2015
DOI: 10.4103/0976-9668.166103
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries status of inmates in central prison, Chennai, Tamil Nadu, India

Abstract: Aim:To understand the dental health among prison inmates, we assessed the dental caries status of central prison inmates in Chennai, India.Materials and Methods:A total of 1060 inmates from three divisions of the central prison in Chennai were assessed by a single investigator for dental caries status based on World Health Organization specifications.Results:Among the inmates, 58.2% of males and 54.2% of females had decayed teeth. About 4.1% of males and 2.9% of females had filled teeth. The mean decayed, miss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 11 publications
1
12
0
2
Order By: Relevance
“…The prevalence of dental caries in this study was 54.14%. This was in line with results obtained from a small number of studies 27 - 29 , while studies conducted by Anup et al, 4 Dhanker K et al, 13 Osborn M et al 15 show a prevalence of caries that is higher. The mean DMFT in this study is very low at 1.93; a similar low mean value was observed by Bolin K et al, 30 Agrawal N. 31 However, higher values of mean DMFT ranging from 9.8 to 22.5 were reported in the systemic review by Walsh T et al 21 The mean DMFT for the prisoners increased with age, as is the norm for any population.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The prevalence of dental caries in this study was 54.14%. This was in line with results obtained from a small number of studies 27 - 29 , while studies conducted by Anup et al, 4 Dhanker K et al, 13 Osborn M et al 15 show a prevalence of caries that is higher. The mean DMFT in this study is very low at 1.93; a similar low mean value was observed by Bolin K et al, 30 Agrawal N. 31 However, higher values of mean DMFT ranging from 9.8 to 22.5 were reported in the systemic review by Walsh T et al 21 The mean DMFT for the prisoners increased with age, as is the norm for any population.…”
Section: Discussionsupporting
confidence: 89%
“…La prevalencia de caries en este estudio fue de 54,14%. Este hecho concuerda con los resultados obtenidos en unos pocos estudios [27][28][29] , mientras los estudios de Anup et al 4 , Dhanker et al 13 , Osborn et al 15 muestran una prevalencia más elevada de caries. El CPO medio en este estudio es muy bajo (1,93); se observó un valor bajo similar en un estudio de Bolin et al 30 y Agrawal 31 .…”
Section: Discussionunclassified
“…Despite such an organization, the health care system for prisoners is inadequate, and in the field of dentistry, it is implemented in external locations, which influences its availability. Several studies have reported the oral health status of prison populations and have shown a high prevalence of dental caries, oro-mucosal lesions, precancerous lesions, poor periodontal status, and missing teeth [ 4 , 7 , 8 , 9 , 10 ]. An extensive review of the literature revealed that the few studies carried out in a prison setting showed a higher prevalence of dental caries and periodontal diseases [ 5 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…[2] Many oral health surveys have targeted children, adolescents, and adults from the normal population. [3] Among these groups, Prisoners are unique population with many oral health problems. [4] Prisoners are psychologically, socially, morally and economically affected group, which makes them to neglect their oral health.…”
Section: Introductionmentioning
confidence: 99%